Å satse på dosenter Et utviklingsarbeid - Bachke, Carl Christian; Hermansen, Mads (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"From an international standpoint, the docent position in Norway is unique, insomuch as it is a top academic position equivalent to a professorship. This book combines a thorough examination of the docent's role and place within the higher educational system with a presentation of a development project to move associate professors up the career ladder to the docent level at the University of Agder (UiA). The first part of the book looks at the Norwegian docent in historical, current and R&D theoretical perspectives. In the second part, six docents relate their own paths to qualification for the position. Part 3 presents the rationale behind the UiA project and how it was executed and subsequently evaluated. The final part of the book analyzes the docent's current and future challenges. Criteria for promotion and expert committee rulings are among the topics discussed. Å satse på dosenter can be read as a practical introduction for docents on how to manage a promotion seminar, but it can also be read as a contribution to the discussion on how to improve research, teaching and communication at universities and colleges. The book will be of particular interest to docents and candidates for the docent position, members of expert committees and administrators at various levels within higher educational institutions. As a contribution to the debate on higher education's need for different profiled positions, the book is relevant for a broader audience of researchers, politicians and public servants in Norway and the other Scandinavian countries. The book has been edited by Carl Christian Bachke, docent emeritus at the University of Agder, and Mads Hermansen, PsyD and professor emeritus at University of Agder."